Construction and validation of a Negative Attitudes toward Trans People Scale - Páez, José (2015)
The study goal was to construct and psychometrically validate a negative’s attitudes towards trans people scale (EANT) as an expression of prejudice against trans. Two interdepen- dent sequential studies through questionnaires are reported, both rely on non-probabilistic samples: Study 1, involves 203 participants, mainly college students, addresses the construction and exploratory analysis of the EANT. Study 2, involving 408 participants assigned according to s ociodemographic quotes established by the national census in the general population, shows confirmatory factor analysis and external validation of the scale. A sole factor 9-item instrument, with acceptable internal consistency (? = .886) was obtained. The results suggest good applicability in general population studies. Expected relations with typical variables (ATLG, RWA, SDO and religiosity) were procured.